2001
DOI: 10.1046/j.1365-2443.2001.00433.x
|View full text |Cite
|
Sign up to set email alerts
|

Werner helicase relocates into nuclear foci in response to DNA damaging agents and co‐localizes with RPA and Rad51

Abstract: Background: Werner syndrome (WS) is an autosomal recessive disorder with many features of premature ageing. Cells derived from WS patients show genomic instability, aberrations in the S-phase and sensitivity to genotoxic agents. The gene responsible for WS (WRN) encodes a DNA helicase belonging to the RecQ helicase family. Although biochemical studies showed that the gene product of WRN (WRNp) interacts with proteins that participate in DNA metabolism, its precise biological function remains unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
133
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(149 citation statements)
references
References 45 publications
15
133
1
Order By: Relevance
“…54 A lot of evidence strongly supports the idea that the biologically relevant function of WRN is related to the repair of stalled replication forks: the S-phase prolongation observed in Werner syndrome (WS) cells; 55 the extreme sensitivity of WS cells to drugs that block replication fork progression; 55-57 the reported requirement of WRN in the correct and fruitful recovery from replication fork arrest. 56,58,59 Although how each biochemical activity of WRN contributes to its function is not fully clarified, several studies indicate specific involvement in different metabolic processes. [60][61][62][63][64][65][66][67] Moreover, WS cells have an elevated spontaneous yield of DNA breakage, which is consistent with the observed high rate of chromosomal rearrangements, 56,68 and depends on an alternative pathway, probably involving break-induced replication, to recover stalled replication forks.…”
Section: Werner Helicase and Common Fragile Site Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…54 A lot of evidence strongly supports the idea that the biologically relevant function of WRN is related to the repair of stalled replication forks: the S-phase prolongation observed in Werner syndrome (WS) cells; 55 the extreme sensitivity of WS cells to drugs that block replication fork progression; 55-57 the reported requirement of WRN in the correct and fruitful recovery from replication fork arrest. 56,58,59 Although how each biochemical activity of WRN contributes to its function is not fully clarified, several studies indicate specific involvement in different metabolic processes. [60][61][62][63][64][65][66][67] Moreover, WS cells have an elevated spontaneous yield of DNA breakage, which is consistent with the observed high rate of chromosomal rearrangements, 56,68 and depends on an alternative pathway, probably involving break-induced replication, to recover stalled replication forks.…”
Section: Werner Helicase and Common Fragile Site Stabilitymentioning
confidence: 99%
“…Similarly, WRN appears to be essential for fruitful rescue from replication fork arrest 56,58,59 and is targeted for phosphorylation by ATR upon replication arrest. [83][84][85][86] Interestingly, we found that WRN regulates CFS stability acting in a pathway associated with ATR-mediated checkpoint response.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…WRN links to BER include physical and functional interaction with polβ , polδ (Szekely et al, 2000), replication protein A (RPA) (Brosh et al, 1999), flap endonuclease 1 (FEN-1) (Brosh et al, 2001b), PCNA (Lebel et al, 1999) and poly(ADP-ribose)polymerase 1 (PARP-1) (von Kobbe et al, 2003a). Possible roles in the HRR pathway are suggested by interactions with the MRN complex (Cheng et al, 2004) and Rad52 (Baynton et al, 2003) and by colocalization with Rad51 in camptothecin-treated cells (Sakamoto et al, 2001). Similarly, a link to the NHEJ pathway is indicated by in interactions of WRN with the NHEJ-essential protein kinase DNA-PK (Yannone et al, 2001,Karmakar et al, 2002a,Li and Comai, 2002.…”
Section: Double-strand Breaks Base Excision Repair and Wrnmentioning
confidence: 99%
“…The substrate specificity of WRN helicase and exonuclease activities has been determined in vitro, and includes a variety of intermediates produced during DNA replication, recombination and repair (Shen et al, 1998;Xue et al, 2002). WRN has been shown to predominantly localize to the nucleolus, but after certain types of DNA damage, leaves the nucleolus and forms distinct foci in the nucleoplasm (Sakamoto et al, 2001;Karmakar and Bohr, 2005;Li et al, 2005). The formation of these foci likely reflects an important stage in the DNA damage response.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of these foci likely reflects an important stage in the DNA damage response. Although the number of WRN-containing nuclear foci increases after replication fork arrest and upon DNA damage (Szekely et al, 2000;Sakamoto et al, 2001), the significance of the formation of these foci and how they are regulated remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%